2003
DOI: 10.1044/1058-0360(2003/056)
|View full text |Cite
|
Sign up to set email alerts
|

Speech Evaluation and Treatment for Patients With Cleft Palate

Abstract: This compendium has been written in conjunction with a cleft lip and palate surgical mission that took place in Villahermosa, Mexico, February 4-9, 2001. Fifty children, 10 per day, received lip or palate surgery. This report, available in both English and Spanish, is intended as a practical and concise guide to basic aspects of evaluation and treatment of speech disorders associated with cleft palate. More detailed and comprehensive sources dealing with this topic are available and have been reviewed by D. P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
1
10
1
2
Order By: Relevance
“…Most of them (76%) had CAD (10% had functional articulation disorders and 67% had functional articulation and CAD). This confirmed that children with CP ± L had typical characteristics of cleft speech types and supports previous studies [26,27]. When data from the first assessment ( Table 2) were compared with the formal articulation test in the second or later visits (Table 3), the results showed the number of children with CP ± L who had normal articulation decreased from 5 (12%) to 3 children (7%).…”
Section: Discussionsupporting
confidence: 88%
“…Most of them (76%) had CAD (10% had functional articulation disorders and 67% had functional articulation and CAD). This confirmed that children with CP ± L had typical characteristics of cleft speech types and supports previous studies [26,27]. When data from the first assessment ( Table 2) were compared with the formal articulation test in the second or later visits (Table 3), the results showed the number of children with CP ± L who had normal articulation decreased from 5 (12%) to 3 children (7%).…”
Section: Discussionsupporting
confidence: 88%
“…Motor-oriented speech therapy should be applied in the majority of the patients in order to modify the atypical production of disordered speech sounds by teaching the correct place and manner of articulation for a single phoneme at a time [51]. Early initiation of the therapy is preferred, as it is easier to eliminate compensatory articulations initially than to treat them subsequently [52]. Correction of the vulnerable plosive /d/ and fricatives /s, z, v/ would be recommended in many patients of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, velopharyngeal dysfunction persists in 7 to 30% of the patients, despite anatomical repositioning of the muscles during surgery, [5], [6], [10]–[12]. This results in speech abnormalities [13]. Various factors such as age at the time of the surgery, skills and experience of the surgeon, type and extension of the cleft, and damage of the motor and proprioceptive nerves have been attributed to suboptimal repair [5], [14]–[16].…”
Section: Introductionmentioning
confidence: 99%